Televisi sebagai Media Sosialisasi Masyarakat Ekonomi ASEAN (MEA) di Indonesia - Kresnawati, Megahnanda Alidyan; Kusuma, Ade (Global and Policy Journal of International Relations, 2020)
Globalization is known since the late 19th century and early 20th century. It can be defined as theprocess of interconnectedness and influence among people throughout the world, in all aspects oflife. There are no boundaries of time and space between nations, led to global bussiness, free trade,migration, cultural and mindset exchange. Since December 31, 2015 the Southeast Asia countries areengaged in ASEAN Economic Community (AEC), which is form of consolidation the economicintegration of the Southeast Asia region, and based on four economic pillars; single market andproduction base, competitive economic region, equitable economic development, and integration inglobalized economy. Indonesia as a third world country, which have the largest population in theSoutheast Asia should have a good opportunity to join and compete in world trade and globalbussiness. This opportunity must be accompanied by the readiness of the government and allelements of society. On the other hand, the AEC can be a form of non-traditional threat to the socialand economic conditions of Indonesia. Based on human security concept, this study using textualanalysis will identifying forms of socialization by television about the Asean Economic Community(AEC) which already done by goverment to society. This paper also provide a strategic role andutilization of television as mass media, to give information and explanation, also educate related tothe challenges of goverment and all elements of society to facing the ASEAN Economy Community.Keywords : ASEAN Economic Community (AEC), Socialization, TelevisionGlobalisasi dikenal sejak akhir abad ke-19 dan awal abad ke-20. Ini dapat didefinisikan sebagaiproses keterkaitan dan pengaruh di antara orang-orang di seluruh dunia, dalam semua aspekkehidupan. Tidak ada batasan waktu dan ruang antar negara, yang mengarah pada bisnis global,perdagangan bebas, migrasi, pertukaran budaya dan pola pikir. Sejak 31 Desember 2015 negaranegaraAsia Tenggara terlibat dalam Masyarakat Ekonomi ASEAN (MEA), yang merupakanbentuk konsolidasi integrasi ekonomi kawasan Asia Tenggara, dan didasarkan pada empat pilarekonomi; pasar tunggal dan basis produksi, kawasan ekonomi kompetitif, pembangunan ekonomiyang adil, dan integrasi dalam ekonomi global. Indonesia sebagai negara dunia ketiga, yangmemiliki populasi terbesar di Asia Tenggara harus memiliki peluang yang baik untuk bergabungdan bersaing dalam perdagangan dunia dan bisnis global. Peluang ini harus dibarengi dengankesiapan pemerintah dan semua elemen masyarakat. Di sisi lain, MEA dapat menjadi bentukancaman non-tradisional terhadap kondisi sosial dan ekonomi Indonesia. Berdasarkan konsepkeamanan manusia, penelitian ini menggunakan analisis tekstual akan mengidentifikasi bentukbentuksosialisasi oleh televisi tentang Masyarakat Ekonomi Asean (MEA) yang sudah dilakukanoleh pemerintah kepada masyarakat. Makalah ini juga memberikan peran strategis danpemanfaatan televisi sebagai media massa, untuk memberikan informasi dan penjelasan, jugamengedukasi terkait tantangan pemerintah dan semua elemen masyarakat untuk menghadapiMasyarakat Ekonomi ASEAN.Kata kunci: Masyarakat Ekonomi ASEAN (MEA), Sosialisasi, Televisi DOI : https://doi.org/10.33005/jgp.v8i01.2170